Evolution of a Spanish Cohort of Patients With Autoinmune Hepatitis (Revista de Medicina Clinica, 2020)
Introduction: There is slight evidence about natural history of autoimmune hepatitis and its management in a real setting in Spain. Aim: To assess the evolution in clinical practice of patients with AIH and analyse the prognostic factors related to it. Methods: All patients with AIH diagnosed in our hospital from January 2000 to December 2018 were included. Results: 84 patients (77% women; age 51,9 years (SD:17) were included, with a prevalence of 22 cases/100.000 inhabitants and a incidence of 1.2 annual cases/100.000 inhabitants. At the time of diagnosis 15% of them had cirrhosis. After induction treatment 70,2% of them reached biochemical remission with a mean of 190 days. About 38% patients required second line treatment, being 40% of them with mycophenolate mofetil. The reason of treatment change was 84% due to side effects, 9% because of inefficacy and 7% owing to a better side-effects profile. Treatment was interrupted in 24 patients (28%) because of biochemical remission after a mean time of treatment of 5,8 years (SD 38 years) with a posterior relapse of 45,8%.Â  No patient required hepatic transplantation and only one patient died because of a variceal bleeding. No significant prognostic factors related to AIH evolution were found. Conclusion: In our reference area the prevalence of AIH was 22 cases/100.000 inhabitants. Biochemical remission was reached in most of our patients. However one third of them required a change in treatment strategy, mainly due to side effects related to azathioprine. No significant prognostic factors related to AIH evolution were found.
Keywords: autoimmune hepatitis; prognostic factors; natural history